2016
DOI: 10.1111/acel.12494
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency in the anti‐aging gene Klotho promotes aortic valve fibrosis through AMPK α‐mediated activation of RUNX 2

Abstract: SummaryFibrotic aortic valve disease (FAVD) is an important cause of aortic stenosis, yet currently there is no effective treatment for FAVD due to its unknown etiology. The purpose of this study was to investigate whether deficiency in the anti‐aging Klotho gene (KL) promotes high‐fat‐diet‐induced FAVD and to explore the underlying molecular mechanism. Heterozygous Klotho‐deficient (KL +/−) mice and WT littermates were fed with a high‐fat diet (HFD) or normal diet for 13 weeks, followed by treatment with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 45 publications
(70 reference statements)
0
26
0
Order By: Relevance
“…The histological and IHC analysis was performed as described in our recent studies (Chen, Lin & Sun, 2016; Gao et al., 2016; Lin, Chen & Sun, 2016; Lin & Sun, 2015a,b; Varshney, Ali, Wu & Sun, 2016). For details, see Data S1.…”
Section: Methodsmentioning
confidence: 99%
“…The histological and IHC analysis was performed as described in our recent studies (Chen, Lin & Sun, 2016; Gao et al., 2016; Lin, Chen & Sun, 2016; Lin & Sun, 2015a,b; Varshney, Ali, Wu & Sun, 2016). For details, see Data S1.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to its anti-aging function, α-KL serves an essential role in the phosphatonin FGF23 signaling pathway and secreted KL functions as an endocrine hormone ( 19 ). Previous studies have identified that α-KL is associated with a range of diseases, including periodontitis ( 20 ), cardiovascular disease ( 21 ) and kidney disease ( 18 ). However, the role of α-KL in hemopathies, including anemia, remains unclear.…”
Section: Generation and Function Of Klmentioning
confidence: 99%
“…Klotho levels in the kidney and blood were lower in patients with CKD [15]. Klotho-deficient mice suffer from a wide variety of age-related disorders as well as tissue calcification, including aortic valve calcification [16, 17]. However, it remains unknown whether Klotho suppresses high Pi-induced osteogenic responses in human AVICs.…”
Section: Introductionmentioning
confidence: 99%